Review of modern microwave filtering devices and their methods of construction - Бойко, Ю. П.; Приходько, Т. Ю.; Басюк, І. О. (Science-based technologies, 2018)
It is well known that oscillatory systems play an extremely high role in radio engineering. The resonators are oscillatory systems for the ultrahigh frequency range that representing a large and significant class of superhigh frequency devices. The article provides an overview of modern superhigh frequency filtering devices, recent interpretations about their main properties and methods of construction. An important factor that defines an issue of filter composition is the transition to integrated circuits containing elements with distributed parameters which accompanied by a number of undesirable phenomena: Q-factor, parasitic bandwidth and wave types of oscillations. The research has shown that the optimization of the design factors of oscillatory systems in such a way that their frequency characteristics are changed, will reduce the losses of the resonators.